Carotenoid charge transfer states and their role in energy transfer processes in LH1-RC complexes from aerobic anoxygenic phototrophs - Šlouf, Václav; Fuciman, Marcel; Dulebo, Alexander; Kaftan, David; Koblížek, Michal; Frank, Harry A; Polívka, Tomáš (The journal of physical chemistry. B, 2013)
Light-harvesting complexes ensure necessary flow of excitation energy into photosynthetic reaction centers. In the present work, transient absorption measurements were performed on LH1-RC complexes isolated from two aerobic anoxygenic phototrophs (AAPs), Roseobacter sp. COL2P containing the carotenoid spheroidenone, and Erythrobacter sp. NAP1 which contains the carotenoids zeaxanthin and bacteriorubixanthinal. We show that the spectroscopic data from the LH1-RC complex of Roseobacter sp. COL2P are very similar to those previously reported for Rhodobacter sphaeroides, including the transient absorption spectrum originating from the intramolecular charge-transfer (ICT) state of spheroidenone. Although the ICT state is also populated in LH1-RC complexes of Erythrobacter sp. NAP1, its appearance is probably related to the polarity of the bacteriorubixanthinal environment rather than to the specific configuration of the carotenoid, which we hypothesize is responsible for populating the ICT state of spheroidenone in LH1-RC of Roseobacter sp. COL2P. The population of the ICT state enables efficient S1/ICT-to-bacteriochlorophyll (BChl) energy transfer which would otherwise be largely inhibited for spheroidenone and bacteriorubixanthinal due to their low energy S1 states. In addition, the triplet states of these carotenoids appear well-tuned for efficient quenching of singlet oxygen or BChl-a triplets, which is of vital importance for oxygen-dependent organisms such as AAPs.
Keywords: kinetika; xanthofyly; světlosběrné proteinové komplexy; Rhodobacter sphaeroides; Energy Transfer; bakteriochlorofyly; Roseobacter; zeaxanthiny; Carotenoids; karotenoidy; Sphingomonadaceae; Xanthophylls; Bacterial Proteins; Zeaxanthins; Light-Harvesting Protein Complexes; Kinetics; přenos energie; Bacteriochlorophylls; bakteriální proteiny